Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.2 - Rational Exponents - Exercise Set: 72



Work Step by Step

$x^{-\frac{3}{4}}+3x^{\frac{1}{4}}=x^{-\frac{3}{4}}(1)+x^{-\frac{3}{4}}(3x^{\frac{4}{4}})=x^{-\frac{3}{4}}(1+3x^{\frac{4}{4}})=x^{-\frac{3}{4}}(1+3x)$ In this problem, we make use of the product rule, which holds that $a^{m}\times a^{n}=a^{m+n}$. For example, $x^{-\frac{3}{4}}\times x^{\frac{4}{4}}=x^{(-\frac{3}{4}+\frac{4}{4})}=x^{\frac{1}{4}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.